(untitled) (Comprehensive Journal of Science, 2025)
This paper examines technical and operational challenges associated with integrating renewable energy sources (RES) — primarily solar photovoltaic (PV) and wind — into modern electrical power grids. The study provides a methodology for analyzing intermittency, grid stability, and mitigation strategies such as energy storage and advanced power-electronic controls. MATLAB scripts and a Simulink model generator are provided to reproduce the case studies and figures.